2011
DOI: 10.3389/fgene.2011.00050
|View full text |Cite
|
Sign up to set email alerts
|

Clusters of adaptive evolution in the human genome

Abstract: Considerable work has been devoted to identifying regions of the human genome that have been subjected to recent positive selection. Although detailed follow-up studies of putatively selected regions are critical for a deeper understanding of human evolutionary history, such studies have received comparably less attention. Recently, we have shown that ALMS1 has been the target of recent positive selection acting on standing variation in Eurasian populations. Here, we describe a careful follow-up analysis of ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…A striking feature of genome scans for positive selection in humans is that they reveal many candidate SNPs that have very similar geographic distributions, with high contrasts observed between continental groups [48,49], and where Africa and America show the largest number of loci with extreme frequency differences [50]. Simulations have shown that such large continental differences could simply arise from surfing of neutral variants during the out of Africa expansion [51].…”
Section: Surfing or Adaptive Evolution?mentioning
confidence: 99%
“…A striking feature of genome scans for positive selection in humans is that they reveal many candidate SNPs that have very similar geographic distributions, with high contrasts observed between continental groups [48,49], and where Africa and America show the largest number of loci with extreme frequency differences [50]. Simulations have shown that such large continental differences could simply arise from surfing of neutral variants during the out of Africa expansion [51].…”
Section: Surfing or Adaptive Evolution?mentioning
confidence: 99%
“…However, several studies have also focused on identifying signatures of polygenic selection 44 and of selection on gene pathways 4 that are involved in a given phenotype, as the biological phenotype is what contributes to the overall reproductive fitness. This approach has been used in cases in which the pathway of interest has been known a priori or is reasonably well annotated 21,47,4953 , such as the hypoxia-inducible factor 1 (HIF1) pathway, which is involved in the physiological response to hypoxic conditions at high altitude. However, in cases in which the biological pathway is not well understood or well annotated, this is a more difficult and complex problem that will require better annotation of gene function, as well as more sophisticated statistical approaches.…”
Section: Identifying Signatures Of Selectionmentioning
confidence: 99%
“…Apart from East Asia, the ITGAL region showed signals of positive selection in other geographic regions (America with XP-CLR, and Sub-Saharan Africa and Oceania with XP-EHH), arguing for a different evolutionary history from that of VKORC1 , which was only found in East Asia. This observation emphasizes the need for studying the geographic distribution of a selective event in a wide range of genetically diverse populations, as per Scheinfeldt et al [49] who, after performing a detailed analysis of a 3 Mb region surrounding a gene showing strong footprints of positive selection, discovered patterns of genetic variation consistent with the presence of a cluster of three independent selective events occurring in different populations. By extending their analysis to the entire genome, they identified several other genomic regions exhibiting evidence for the presence of multiple and independent selective targets, suggesting that clusters of adaptive evolution, such as the one detected herein, are widespread in the human genome.…”
Section: Discussionmentioning
confidence: 67%